Major problems with paediatric bed usage statistics?. Issue 4 (April 1991) - MacFaul, R; Long, R
Abstract : This study was carried out on the way in which children's beds were used by the specialty of paediatrics in a district general hospital. Five differing ways were found of interpreting the present Department of Health guidelines on health services information (Körner recommendations). These gave bed occupancy figures varying between 73% and 106%; throughput figures varying between 23.8 and 34.7 discharges per bed; and turnover interval varying between -0.17 and 1.1 days for the same group of paediatric admissions. For comparisons of efficiency and costs between hospitals, which are based upon bed utilisation statistics, it is essential that there is standardisation of method of analysis.